LARVICULTURA DE PIAU CORRÓ (Leporinus lacustris) EM DIFERENTES MANEJOS ALIMENTARES - ORUÊ, Andrey Makálister Souza,; MACHADO, João victor Bezerra,; ROMERO, João Pedro Alves,; SANTOS, Jussara Garrido dos,; ACUNHA, Rubia Mara Gomes,; COSTA, Deliane Cristina, (ANAIS DO ENIC, 2023)
-